THE DEVELOPMENT OF THE COMPLEX SOCIETY IN THE VALLEY OF CASMA - Pozorski, Sheila (2000)
Complex cities developed near groups of monumental mounds in the Casma Valley around 1500 b.C. during che Inicial period or Early Formative. To date, the best-known of these sites is Pampa de las Llamas-Moxeke, however, this is only one of several sites in the valley that date to this time period and to the previous time period, the Late Preceramic. This arride examines the origins of some characteristics and ideas present in Late Preceramic sites that are further developed in Inicial period sites such as Pampa de las Llamas-Moxeke. In addition, the nature of urbanism at Pampa de las Llamas-Moxeke is discussed as well as the relationship of that site with other contemporaneous sites in the valley such as Taukachi-Konkán and Sechín Alto.